2020
DOI: 10.15788/mwc202011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Irrigation Efficiency: Toward a Sustainable Water Future for Montana

Abstract: Water is our most valuable natural resource, and is used to support the demands of industry, agriculture, hydroelectric power generation, and municipalities. Water also sustains Montana’s booming recreation and tourism economy and maintains the diverse freshwater ecosystems that provide natural goods and services and promote human well-being. As our population continues to grow, and the collective demand for water increases, it is imperative that we carefully assess how our water is used, as well as how change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Increased irrigation efficiency and its negative effects on recharge have also been widely documented in the GYA's river valleys (venn et al 2004;Kendy and Bredehoeft 2006;Lonsdale et al 2020). Thus, these aquifers are susceptible to the effects of climate change through loss of natural recharge, as well as through the same feedback mechanism observed on the Eastern Snake Plain Aquifer.…”
Section: Groundwater and Climate Change In Idahomentioning
confidence: 99%
See 1 more Smart Citation
“…Increased irrigation efficiency and its negative effects on recharge have also been widely documented in the GYA's river valleys (venn et al 2004;Kendy and Bredehoeft 2006;Lonsdale et al 2020). Thus, these aquifers are susceptible to the effects of climate change through loss of natural recharge, as well as through the same feedback mechanism observed on the Eastern Snake Plain Aquifer.…”
Section: Groundwater and Climate Change In Idahomentioning
confidence: 99%
“…Careful irrigation practices provide an opportunity to recharge groundwater to buffer climate-driven impacts in the future. A water management strategy called managed aquifer recharge (intentional introduction of water into aquifers through injection wells or seepage ponds) allows aquifers to serve as large natural reservoirs, increasing the resilience of both surface water and groundwater supplies to climate change (Lonsdale et al 2020). Important fish and wildlife habitat in GYA's valley areas can be maintained and enhanced in a warming climate with carefully planned managed aquifer recharge (Kendy and Bredehoeft 2006;van Kirk et al 2020).…”
Section: Groundwater and Climate Change In Idahomentioning
confidence: 99%
“…Throughout this paper return flow is used to describe the additional groundwater discharge to a stream resulting from irrigation. The additional groundwater baseflow provided by return flows can be an important component of the seasonal water balance of irrigated alluvial aquifers and provide an additional source of flow during critical low-discharge periods (Venn et al, 2004;Kendy and Bredehoeft, 2006;Fernald et al, 2010;Lonsdale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Colorado subbasin where flood irrigation is the primary method of irrigation, mean annual return flows are estimated to be on the order of hundreds of thousands of acre feet per year (∼0.1-1 km 3 ) (Colorado Department of Water Resources, 2016). Another example is provided by a recent study by Lonsdale et al (2020) in Montana where flood irrigation is also common. They found that of the 10.5 million-acre feet (12.95 km 3 ) that are on average diverted annually for irrigation, almost 8 million acre-feet (9.86 km 3 ) are not consumed and likely contribute to groundwater recharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation